Divisibilidade em domínios de integridade - Sousa, Márcio Monte Alegre (2013)
This paper is aimed to study the divisibility in integrality domain. So, it was structured that way: at first it is done a basic approach which will be a pre domain for its development, right after it will be done a study about Euclidean domain and Gaussian integer domains culminating in the enforcement of the results gotten in the characterization of prime ideals Gaussian s integers ring.